2014
DOI: 10.1073/pnas.1316177111
|View full text |Cite
|
Sign up to set email alerts
|

Origin of regenerating tubular cells after acute kidney injury

Abstract: Significance Acute kidney injury (AKI) is a common and significant clinical problem for which no specific therapy has been developed. There is controversy about the origin of the regenerating tubular cells after AKI. Attention has recently focused on “scattered tubular cells” (STCs), which are by far the best candidate cells for the postulated fixed progenitor population of kidney tubular cells. In the present study, we clarify this question by genetic cell fate labeling using a unique transgenic mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
128
3
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(140 citation statements)
references
References 22 publications
6
128
3
3
Order By: Relevance
“…[21][22][23][24] These works hypothesized that these cells might represent a committed intratubular stem cell population. [21][22][23][24] To address this controversy, Kusaba et al 25 and Berger et al 26 have used transgenic mice to genetically label this scattered tubular cell population. Both groups independently concluded that scattered tubular cells do not represent a fixed progenitor population but rather, a phenotype that can be adopted by almost any proximal tubular cell on injury.…”
Section: Mechanisms Of Normal Repairmentioning
confidence: 99%
“…[21][22][23][24] These works hypothesized that these cells might represent a committed intratubular stem cell population. [21][22][23][24] To address this controversy, Kusaba et al 25 and Berger et al 26 have used transgenic mice to genetically label this scattered tubular cell population. Both groups independently concluded that scattered tubular cells do not represent a fixed progenitor population but rather, a phenotype that can be adopted by almost any proximal tubular cell on injury.…”
Section: Mechanisms Of Normal Repairmentioning
confidence: 99%
“…Second, in a previous study we detected ANXA3 in a specific population of proximal tubular cells of the kidney, the so-called scattered tubular cells. 19,20 Scattered tubular cells express similar proteins as PECs. In the present study, we found that within the glomerulus ANXA3 was expressed exclusively by PECs and infiltrating leukocytes 21 ( Figure 7D).…”
Section: Detecting Pecs In Sclerotic Lesions By Using Akap12 or Anxa3mentioning
confidence: 99%
“…The PEC transgenic mouse line recapitulated this program because it also labeled STCs with high sensitivity in the proximal tubule and allowed us to trace these cells in vivo. 10 Our results showed that any tubular cell may transiently acquire the STC phenotype, which is a specific transcriptional program in response to virtually any tubular injury. We found no experimental support for STCs representing a fixed intrinsic progenitor population.…”
Section: Search For Progenitor Cells In the Proximal Tubulementioning
confidence: 54%
“…These markers are also part of the common transcriptional program and are expressed by both PECs and proximal tubular cells with the STC phenotype. 10 When culturing urinary PECs and proximal tubular cells, one can expect that they will activate the common STC transcriptional program in response to stimulatory culture conditions as used by Lazzeri et al (the authors used 20% FCS supplemented with a mixture of growth factors) so that many of them may acquire an RPC phenotype (i.e., coexpressing RPC markers, including CD24 and glyCD133). Further characterization of the cell populations isolated by Lazzeri et al will therefore be required in future studies.…”
Section: Search For Progenitor Cells In the Proximal Tubulementioning
confidence: 99%